(untitled) (Indian Journal of Animal Production and Management, 2016)
The present study attempts to analyze the effect of supplementation of Ajwain on the Haemato-biochemical parameters of broiler chicken. Two hundred and twenty five day old straight run broiler chicks were distributed into 5 groups with 3 replicates, each consisting of 15 broilers in a completely randomized design. The treatments included the control group (basal diet) and four groups with basal diet + Ajwain powder @ 0.1% in feed, basal diet + Ajwain powder @ 0.2% in feed and basal diet + Ajwain seeds soaked in drinking water over nightly @ 0.1% and basal diet + Ajwain seeds soaked in drinking water over nightly @ 0.2% respectively. Temperature and humidity of the shed were recorded daily to calculate Temperature Humidity Index (THI). Standard feeding and all other managemental practices were followed during the experimental period. At 14, 28 and 42nd day of the experiment, one bird from each replicate was sacrificed for estimation of Haemato-biochemical parameters. Among Haemato-biochemical parameters Hb, PCV, TEC, TLC, cholesterol, calcium, phosphorus, magnesium and total protein showed significant differences among treatment groups as compared to control group.